A new perspective in grid connection of electric vehicles: Different operating modes for elimination of energy quality problems - Boynuegri, A. R.; Uzunoglu, M.; Erdinc, O.; Gokalp, E. (ELSEVIER SCI LTD, 2014)
Lately, the depletion as well as negative environmental impacts of fossil fuels have directed the vehicle technology towards new alternative systems. Accordingly, the studies on electric vehicles (EVs) utilizing electric motor (EM) instead of conventional vehicles using fossil fuel consumer internal combustion engines (ICEs) have gained increasing importance. The EV technology firstly developed with the hybrid vehicles using both ICE and EM. Today, plug-in hybrid vehicles that can be charged via the grid have a leading position. Studies realized in many countries all over the world manifest the result of future widespread EV utilization. However, the power management and grid connection of EVs still comprise many unsolved problems. In this study, a power management is realized in order to reduce the battery stress of EVs and to solve the possible problems that can be faced while providing grid connection. In order to realize power management in charging process, smart grid is strongly necessary. For this reason, smart grid compatible relevant power converters are employed. A power conditioning unit is designed for the grid connection of EV enabling a controlled charge of the EV. With the utilization of the proposed power conditioning unit within the EV, the possibilities of solving the energy quality problems at the charging point, increasing the voltage quality, decreasing total harmonic distortion (THD) and even providing reactive power compensation by EV are obtained. The relevant results are discussed within simulation studies followed by a pre-evaluation of the proposed method with experimental real-time test bench based applications. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Active harmonic filter; Electric vehicle; Energy quality; Grid connection; Reactive power compensation; Smart grid; INTEGRATION; Energy & Fuels; Engineering